Green Supply Chains: A Comparative Efficiency Analysis in the Gulf and Beyond - Alexander Wollenberg (15445424) (2023)
We compare the development of Sustainable (Green) Supply in three regions of the world, the countries of the Gulf Cooperation Council (GCC) in the Middle East, six countries in Europe, and six countries in Latin America, which were selected based on their Logistics Performance Index over a 10-year period. We based our empirical analysis on UN SDGs concerned with clean energy, innovation, sustainable communities, and climate action (SDGs 7, 9, 11, and 13, respectively). Using a modified RAM-DEA model, our results showed high logistics performance but significant divergence in green logistics performance among GCC countries. Countries in Western Europe led in terms of inputs that result in green outputs. Strong contenders in green supply chains include the UAE, Oman, México, Panamá, and Ecuador. Other Information Published in: Social Change and Transformation in the Gulf Region License: https://creativecommons.org/licenses/by/4.0 See chapter on publisher's website: https://dx.doi.org/10.1007/978-981-19-7796-1_28